Framing Analysis of Reporting on the Indigenous People of Laman Kinipan in Online Media Tempo.co and Detik.com from August to September 2020 - Djunaedy, Muhammad Fathi; Rachmat Kriyantono, (Advances in Social Sciences Research Journal, 2023)
This research focuses on how the online media Tempo.co and Detik.com frame the news about the arrest of Effendi Buhing, Chairperson of the Laman Kinipan Indigenous People, from August to September 2020. This research took place from June to July 2022. Researchers use the theory of the hierarchy of influence to understand how to frame information on the arrest of Effendi Buhing. This study used the Zhongdang Pan Gerald Konsicki analysis and framing model. The model uses four structural framings: syntax, script, thematic, and rhetorical. Based on research results, the news presented by Tempo.co is more in favor of Effendi Buhing and the indigenous people of Kinipan. The narrative emphasizes more on the issue that the arrest of Effendi Buhing was a criminal act by the police. Meanwhile, from the 17 Detik.com news articles studied, the results were quite balanced because Detik.com was not too biased in favor of either party. In its report, Detik.com emphasized that the video of Effendi Buhing's arrest had previously gone viral on social media before it became news. Associated with the theory of the hierarchy of influence. At the individual level, Tempo.co quite influenced the framing used by Tempo.co in reporting on the arrest of Effendi Buhing. Meanwhile, at Detik.com, the individual level does not affect the framing of the news about Effendi Buhing's arrest. This research expands on communication studies research, especially media research, namely framing analysis linked to the theory of the hierarchy of influence, with the subject of reporting on indigenous peoples in two Indonesian mainstream media, Tempo.co and Detik.com. The results of this study strengthen the framing theory that the media constructs and frames messages in presenting their news, as done by Tempo.co and Detik.com. Its relation to the theory of the hierarchy of influence, for Tempo.co strengthens the theory of the hierarchy of influence that individual journalists' level factors, in this case, the educational aspect, influences the content of Tempo.co's news, on the other hand, Detik.com media contradicts the theory of the hierarchy of influence, that individual journalists' factors do not affect news content.